PCB drilling using arduino - Tan, Kee Kian (2015)
PCB drilling machine is used to drill holes on the PCB in order to provide component mounting and to make electrical interconnection between the bottom and top of the PCB. PCB drilling machine can be divided into two types. One is Manual Controlled Machines and the other is Computer Numerically Controlled Machine. This project is focusing on the designs and fabricates a prototype of low cost 3 axes PCB drilling machine. Arduino Uno is used as the main controller of the PCB drilling machine to control the motors and other electrical components. The PCB drilling machine is specific designed for single sided PCB only.